Compassionate statistics applied quantitative analysis for social services : with exercises and instructions in SPSS - Faherty, Vincent E. (Vincent Edward), 1939-; Sage eBooks (London : SAGE, 2008)
Faherty provides a comprehensive, yet pragmatic resource for social service professionals to use standard descriptive and inferential statistical techniques in ways that are meaningful to them, to their social agencies, to their funding sources and, ultimately, to their clients.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: SPSS (Computer file); Social sciences -- Statistical methods -- Computer programs; Social service -- Statistical methods; Evaluation research (Social action programs) -- Statistical methods; Electronic books